2014
DOI: 10.1136/jech-2014-204063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2011 Great East Japan Earthquake on community health: ecological time series on transient increase in indirect mortality and recovery of health and long-term-care system

Abstract: This study showed transient increase in indirect mortality and recovery of health and long-term-care system after the earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…A previous study hypothesised that postdisaster increases in pneumonia were caused by the swallowing of dust and water carried by the tsunami 33. However, in our findings, more than half of the patients who died from pneumonia were in inpatient medical facilities at the time of the earthquake, making them unlikely to be directly affected by the tsunami.…”
Section: Discussioncontrasting
confidence: 81%
“…A previous study hypothesised that postdisaster increases in pneumonia were caused by the swallowing of dust and water carried by the tsunami 33. However, in our findings, more than half of the patients who died from pneumonia were in inpatient medical facilities at the time of the earthquake, making them unlikely to be directly affected by the tsunami.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies indicated that the number of hospitalised patients with pneumonia was related to destruction ratios, 21 and showed that the higher percentage of households flooded was associated with a higher risk of indirect mortality. 22 Many tsunami survivors lost their homes and had to flee to shelters in the destroyed environment. The medical staff were not stationed in all shelters.…”
Section: Discussionmentioning
confidence: 99%
“…Expenditure on healthcare and long-term care is useful to investigate health status, care needs, and access to health services (Uchimura et al 2014;Morita et al 2016;Kent et al 2017;Matsuyama et al 2018). All Japanese citizens have public health insurance, whereas long-term care insurances target elders who need care (e.g., meal assistance).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Fukushima disaster, excess weight was associated with higher healthcare costs (Kent et al 2017). Uchimura et al (2014) reported a decline in long-term care expenditure for 1-5 months immediately after the Fukushima disaster and attributed this decline to upheaval (e.g., losses of their house) related to the disaster. reported that the total expenditure on long-term care services in Minamisoma City, an EOA, was 50% higher in 2014 than the pre-disaster level in 2009.…”
Section: Introductionmentioning
confidence: 99%